Potential nutraceutical and food additive properties and risks of coffee: a comprehensive overview. Issue 20 (13th November 2019) - Saeed, Muhammad; Naveed, Muhammad; BiBi, Jannat; Ali Kamboh, Asghar; Phil, Lucas; Chao, Sun
Abstract: Coffee is a composite mixture of more than a thousand diverse phytochemicals like alkaloids, phenolic compounds, vitamins, carbohydrates, lipids, minerals and nitrogenous compounds. Coffee has multifunctional properties as a food additive and nutraceutical. As a nutraceutical, coffee has anti-inflammatory, anti-oxidant, antidyslipidemic, anti-obesity, type-2 diabetes mellitus (DM), and cardiovascular diseases (CVD), which can serve for the treatment and prevention of metabolic syndrome and associated disorders. On the other hand, as a food additive, coffee has antimicrobial activity against a wide range of microorganisms, inhibits lipid peroxidation (LPO), and can function as a prebiotic. The outcomes of different studies also revealed that coffee intake may reduce the incidence of numerous chronic diseases, like liver disease, mental health, and it also overcomes the all-cause mortality, and suicidal risks. In some studies, high intake of coffee is linked to increase CVD risk factors, like cholesterol, plasma homocysteine and blood pressure (BP). There is also a little evidence that associated the coffee consumption with increased risk of lung tumors in smokers. Among adults who consume the moderate amount of coffee, there is slight indication of health hazards with strong indicators of health benefits. Moreover, existing literature suggests that it may be cautious for pregnant women to eliminate the chances of miscarriages and impaired fetal growth. The primary purpose of this narrative review is to provide an overview of the findings of the positive impacts and risks of coffee consumption on human health. In conclusion, to date, the best available evidence from research indicates that drinking coffee up to 3–4 cups/day provides health benefits for most people.